Nanofiber and piezoelectric polymer compounded solid electrolyte membrane, preparation method thereof and secondary battery

Through the solid electrolyte membrane composited by nanofibers and piezoelectric polymers, the problems of uneven dissolution of zinc negative electrodes and low conductivity in zinc ion batteries are solved, and a high-performance zinc ion battery is achieved, with excellent cycle stability and mechanical properties. .

CN119208766AActive Publication Date: 2024-12-27SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411115819.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-27
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The uneven dissolution/deposition of zinc negative electrodes in existing zinc ion batteries leads to dendrite growth, causing short circuits and corrosion problems, and the low ionic conductivity of solid electrolytes, limiting battery performance.

Method used

A solid electrolyte membrane that is composited with nanofibers and piezoelectric polymers is used to prepare nanofiber membranes as a skeleton through electrospinning technology, and piezoelectric polymers and zinc salts are injected to improve ionic conductivity and mechanical properties.

Benefits of technology

It significantly improves the ionic conductivity and structural stability of zinc ion batteries, inhibits zinc corrosion, extends battery life, and improves electrochemical and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208766A_ABST
    Figure CN119208766A_ABST
Patent Text Reader

Abstract

The invention discloses a nanofiber and piezoelectric polymer composite solid electrolyte membrane, a preparation method thereof and a secondary battery, and relates to the technical field of batteries, the raw materials of the solid electrolyte membrane comprise nanofibers and piezoelectric polymers, and the raw materials of the piezoelectric polymers comprise piezoelectric polymers, zinc salt and ionic liquid; the nanofiber serves as a framework in the form of a nanofiber membrane, and the piezoelectric high-molecular polymer is arranged on the nanofiber membrane. The preparation method comprises the following steps: preparing a high polymer material into a spinning solution for spinning treatment to obtain a nanofiber membrane; and dissolving the piezoelectric polymer, the zinc salt and the ionic liquid, uniformly spreading on the nanofiber membrane, and drying to obtain the zinc-doped piezoelectric nanofiber membrane. The secondary battery includes a solid electrolyte membrane. The invention has the following beneficial effects: the nanofiber-reinforced solid electrolyte membrane realizes uniform distribution of current and electric field, and provides ideal conditions for zinc deposition; piezoelectric macromolecules are injected as an ion transmission medium, and zinc salt and ionic liquid are introduced, so that the ionic conductivity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to electrolyte materials in batteries, in particular to a solid electrolyte membrane composited with nanofibers and piezoelectric polymers, a preparation method thereof and a secondary battery, and belongs to the field of new energy materials and electrochemistry. Background Art

[0002] Among the currently commercialized rechargeable secondary batteries, lithium-ion batteries are widely used in hybrid / pure electric vehicles and portable electronic devices due to their high energy density and excellent cycle stability. However, lithium-ion batteries often lose control during the dissolution / deposition process of the negative electrode, forming lithium dendrites. These dendrites may pierce the diaphragm as they grow, causing a short circuit between the positive and negative electrodes. At high current densities, the local heating caused by dendrite growth coupled with flammable organic electrolytes can easily cause safety issues such as fire and explosion. In addition, the scarcity of lithium metal resources leads to high costs, further limiting the application of lithium-ion batteries. Therefore, other high-safety, low-cost rechargeable secondary battery technologies are urgently needed.

[0003] Among many candidate batteries, zinc-ion batteries have become one of the most promising energy storage systems due to their low redox potential, high theoretical capacity, abundant resources and environmental protection. Compared with organic electrolytes, aqueous zinc-ion batteries have lower costs, easier assembly and higher ionic conductivity. However, zinc-ion batteries also face the problem of uneven dissolution / deposition of zinc negative electrodes leading to dendrite growth, which can cause short circuits and affect battery performance. In addition, the corrosion, hydrogen evolution and passivation problems of the zinc negative electrode also need to be solved to improve the cycle life and coulombic efficiency of zinc-ion batteries.

[0004] Compared with liquid electrolytes, polymer electrolytes not only have higher safety and stability, but also have good thermodynamic properties and stable ion transport capabilities. In addition, polymer electrolytes have good mechanical properties and are expected to achieve lightweight and flexible zinc-ion batteries. Therefore, polymer electrolytes occupy an important position in the future development of energy storage. At present, the definition of solid polymer electrolytes and quasi-solid electrolytes is not very clear. Generally, people are accustomed to dividing polymer electrolytes into two categories, namely gel polymer electrolytes and solid polymer electrolytes. The presence or absence of liquid plasticizers in the electrolyte is the main basis for distinguishing solid polymer electrolytes from gel polymer electrolytes. Typical gel polymer matrices include polyvinyl alcohol-based hydrogels, gelatin-based hydrogels, and polyacrylamide-based hydrogels, as well as polymer matrices derived from these gel polymer matrices by physical and chemical methods. However, the currently reported gel electrolytes have poor mechanical strength and Zn 2+The low conductivity limits its application. Compared with gel electrolytes, solid polymer electrolytes not only provide mechanical stability but also eliminate the solvent evaporation problem, thereby stabilizing the electrode / electrolyte interface, so the advantages of solid polymer electrolytes are more obvious.

[0005] Polymer electrolytes can effectively alleviate the dissolution of electrode materials and maintain the relative stability of electrochemical properties, avoiding the leakage and electrolyte volatilization problems of traditional aqueous electrolytes. However, gel polymer electrolytes are not solid electrolytes in the true sense, because their water content is still a hidden danger. The presence of water still limits the voltage window of gel polymer electrolytes. Although the hydrogen evolution reaction can be suppressed within the appropriate voltage window, there are still certain safety hazards after continuous cycle accumulation. In contrast, since solid polymer electrolytes are completely solvent-free and solve the problem of side reactions caused by active water, solid polymer electrolytes have broader prospects. However, the conductivity of the polymer matrix itself is generally poor, and the conductivity is usually around 10 at room temperature. -7 Up to 10 -6 S / cm. Traditional methods such as adding inorganic fillers can increase the conductivity by 1 to 2 orders of magnitude, but it still cannot meet actual needs. In recent years, some innovative work has emerged, such as in-situ synthesis of amorphous polymer electrolytes, which fully exploits the conductivity of the amorphous region and increases the conductivity to 10 -2 In addition to using a single polymer matrix, multiple excellent properties can also be achieved through grafting, blending of multiple polymers, cross-linking, and other methods. Summary of the invention

[0006] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art, and to provide a solid electrolyte membrane composite of nanofibers and piezoelectric polymers and a preparation method and application thereof, so as to solve the problems of low ion conductivity and uneven deposition of metal zinc in the existing solid electrolyte membrane.

[0007] The technical solution of the present invention is as follows:

[0008] In order to achieve the above application purpose, the first aspect of the present invention provides a solid electrolyte membrane composite of nanofibers and piezoelectric polymers.

[0009] The raw materials for preparing the nanofiber and piezoelectric polymer composite solid electrolyte membrane of the present invention include piezoelectric polymer and nanofiber membrane, and the raw materials for preparing the piezoelectric polymer include piezoelectric polymer, zinc salt and ionic liquid;

[0010] The nanofibers are in the form of nanofiber membranes as the skeleton of the solid electrolyte membrane, and the piezoelectric high polymer is disposed on the nanofiber membrane to form the solid electrolyte membrane.

[0011] The technical core of this application is to use nanofibers as the skeleton of the solid electrolyte, then inject piezoelectric polymers as ion conduction media, introduce zinc salts and ionic liquids, and use nanofibers to make up for the problem of insufficient strength of the matching piezoelectric polymer. The solid electrolyte membrane of the nanofibers and piezoelectric polymers in this application has high capacity and high ion conductivity, and excellent properties such as structure and cycle stability, and also has excellent mechanical properties. Its preparation method can ensure that the structure and electrochemical properties of the solid electrolyte membrane are stable and efficient. The zinc ion battery has high capacity, excellent cycle performance, and good rate capability.

[0012] Furthermore, the mass ratio of the nanofiber to the piezoelectric high polymer is 1:2 to 1:10.

[0013] Furthermore, the nanofiber is at least one of polyester, polyamide, polyimide, polyamide-amide, polyimide-amide, polyamide-imide, polyamide-amide-amide, polyvinyl alcohol, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, and polyurethane polymer materials.

[0014] Furthermore, the piezoelectric polymer is at least one of polystyrene, polyvinylidene fluoride, polytrifluoroethylene, polyethylene difluoride, polyethylene vinyl acetate, polychlorotrifluoroethylene and their multi-component copolymers.

[0015] Furthermore, the zinc salt is at least one of zinc chloride, zinc acetate, zinc sulfate, zinc nitrate, and zinc trifluoromethanesulfonate.

[0016] Furthermore, the ionic liquid is at least one of 1-ethyl-3-methylimidazolium zinc nitrate, 1-butyl-trimethylimidazolium zinc nitrate, 1-ethyl-trimethylimidazolium zinc hexafluorophosphate, 1-ethyl-trimethylimidazolium zinc tetrafluoroborate, and 1-ethyl-trimethylimidazolium zinc trifluorosulfonate.

[0017] Furthermore, the contents of raw materials for preparing the piezoelectric high molecular polymer are as follows: the mass percentage content of the piezoelectric high molecular polymer is 30% to 80%, the mass percentage content of the zinc salt is 5% to 35%, and the mass percentage content of the ionic liquid is 5% to 35%.

[0018] The second aspect of the present invention provides a method for preparing a solid electrolyte membrane composite of nanofibers and piezoelectric polymers. The method for preparing a solid electrolyte membrane composite of nanofibers and piezoelectric polymers of the present invention is as follows:

[0019] The polymer material is dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is subjected to spinning treatment to obtain a nanofiber membrane;

[0020] Using an organic solvent to dissolve the piezoelectric polymer, the zinc salt and the ionic liquid, heating and stirring until the mixture is uniform, to obtain a mixed solution;

[0021] The mixed solution is evenly spread on the nanofiber membrane and dried to obtain a piezoelectric polymer.

[0022] The obtained transparent solution is evenly coated on the nanofiber membrane, and left to dry at room temperature to evaporate the solvent. After the solvent is completely evaporated, a solid electrolyte membrane is obtained.

[0023] Further, the spinning process is an electrostatic process, and the conditions of the electrostatic process are as follows:

[0024] The inner diameter of the needle is 0.6-2.2 mm; the voltage is 10-20 kV; the temperature is 35-45 °C, the relative humidity is 43-47% RH, and the propulsion speed is 3-6 mL h -1 , receiving distance is 10~20cm, receiver speed is 100~500rpm.

[0025] Furthermore, in the spinning solution, the mass concentration of the organic solvent is 80% to 90%, and the mass concentration of the polymer material is 10% to 20%.

[0026] Furthermore, the organic solvent includes at least one of N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0027] Furthermore, the heating temperature of the piezoelectric polymer, zinc salt and ionic liquid is 20°C to 95°C.

[0028] Furthermore, the mixed solution is evenly spread on the nanofiber membrane, placed at room temperature, and dried to evaporate and remove the solvent, and the evaporation time is 10 to 60 minutes.

[0029] A third aspect of the present invention provides a secondary battery. The secondary battery of the present invention includes a solid electrolyte, and the solid electrolyte is the solid electrolyte in the present invention.

[0030] Furthermore, the secondary battery is an all-solid-state zinc ion battery, and the solid electrolyte membrane in the all-solid-state zinc ion battery is the solid electrolyte membrane in the present invention.

[0031] The present invention has at least one of the following beneficial effects:

[0032] The present invention proposes a solid electrolyte membrane. By introducing a nanofiber membrane prepared by electrospinning technology as a skeleton material, a composite membrane with high ionic conductivity and excellent interface properties is constructed, which significantly improves the battery performance. This design not only gives the solid electrolyte membrane a high degree of structural stability and interface properties, but also effectively inhibits zinc corrosion. The nanofiber-reinforced solid electrolyte membrane achieves a uniform distribution of current and electric field, providing ideal conditions for zinc deposition. In addition, by injecting piezoelectric polymers as ion transport media and introducing zinc salts and ionic liquids, the ionic conductivity is further improved, providing a more reliable basis for the preparation of electrolyte membranes. The electrolyte has made a significant contribution to inhibiting zinc dendrites.

[0033] The secondary battery provided by the present invention has the advantages of high capacity, excellent cycle performance, and good rate capability, and can be a flexible battery with excellent mechanical properties. Therefore, the secondary battery prepared using the solid electrolyte membrane of the present invention can improve the stability of the electrochemical performance of the secondary battery and extend the life of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a physical picture of a solid electrolyte membrane composited with nanofibers and piezoelectric polymers according to Example A1 of the present application;

[0035] Figure 2 This is a physical picture of the piezoelectric polymer composite solid electrolyte membrane in Comparative Example A1 of the present application;

[0036] Figure 3 A physical picture of a piezoelectric polymer composite solid electrolyte membrane in Comparative Example A4 of the present application;

[0037] Figure 4 This is a scanning electron microscope (SEM) image of a solid electrolyte membrane composited with nanofibers and piezoelectric polymers in Comparative Example A7 of the present application;

[0038] Figure 5 This is a scanning electron microscope (SEM) image of a solid electrolyte membrane composite of nanofibers and piezoelectric polymers in Example A1 of the present application;

[0039] Figure 6 is a dielectric constant curve of the zinc ion battery in Example B1 of the present application;

[0040] Figure 7 This is a comparison diagram of X-ray diffraction of the solid electrolyte membrane of Example A1 of the present application and Comparative Examples A1 and A4;

[0041] Figure 8 This is a comparison diagram of the Raman spectra of the solid electrolyte membranes of Example A1 of the present application and Comparative Examples A1 and A4;

[0042] Fig. 9This is a comparison chart of the electrochemical stability of the solid electrolyte membranes of Example A1 of the present application and Comparative Examples A1 and A4;

[0043] Fig.10 This is a graph of the ionic conductivity of a solid electrolyte membrane composited with nanofibers and piezoelectric polymers in Example A1 of the present application;

[0044] Fig.11 This is a cycle performance diagram of the zinc ion battery in Example B1 of the present application;

[0045] Fig.12 This is a high and low temperature performance curve of the zinc ion battery in Example B1 of the present application;

[0046] Fig.13 This is a cycle performance curve diagram of the zinc-iodine battery in Example B2 of the present application. DETAILED DESCRIPTION

[0047] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] One embodiment of the present invention provides a solid electrolyte membrane, the preparation raw materials include nanofibers and piezoelectric polymers, the preparation raw materials of the piezoelectric polymers include piezoelectric polymers, zinc salts and ionic liquids; the nanofibers are in the form of nanofiber membranes as the skeleton of the solid electrolyte membrane, and the piezoelectric polymer is arranged on the nanofiber membrane to form the solid electrolyte membrane.

[0049] The present invention uses nanofiber membrane as a skeleton material to construct a composite membrane with high ionic conductivity and excellent interface performance, which significantly improves battery performance, not only giving the solid electrolyte membrane a high degree of structural stability and interface performance, but also effectively inhibiting zinc corrosion. The nanofiber-reinforced solid electrolyte membrane achieves uniform distribution of current and electric field, providing ideal conditions for zinc deposition. In addition, by injecting piezoelectric polymers as ion transport media and introducing zinc salts and ionic liquids, the ionic conductivity is further improved, providing a more reliable basis for the preparation of electrolyte membranes and being able to inhibit zinc dendrites.

[0050] In a specific embodiment of the present invention, the nanofibers are formed into nanofiber membranes by electrostatic spinning.

[0051] In a specific embodiment of the present invention, the solid electrolyte membrane is formed by dissolving the raw material for preparing the piezoelectric polymer in a solvent to obtain a solution, and then pouring the solution on the nanofiber membrane. Preferably, the solvent is DMF.

[0052] Since the nanofiber membrane in the present invention is a three-dimensional self-supporting fiber skeleton, that is, a membrane; the raw material for preparing the piezoelectric polymer is dissolved in DMF, and then the solution is obtained and poured on the nanofiber membrane. The solution will penetrate into the skeleton of the nanofiber membrane, and when the solution is solidified, a solid electrolyte membrane is obtained.

[0053] In a specific embodiment of the present invention, the mass ratio of the nanofiber to the piezoelectric polymer is 1:2 to 1:10, preferably 1:2 to 1:8, and more preferably 1:2 to 1:6. Specifically, the mass ratio of the nanofiber to the piezoelectric polymer is 1:2 or 1:2.5 or 1:3 or 1:3.5 or 1:4 or 1:4.5 or 1:5, etc.

[0054] In a specific embodiment of the present invention, the nanofiber is at least one of polyester, polyamide, polyimide, polyamide-amide, polyimide-amide, polyamide-imide, polyamide-amide-amide, polyvinyl alcohol, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, and polyurethane polymer materials.

[0055] In a specific embodiment of the present invention, the piezoelectric polymer is at least one of polystyrene, polyvinylidene fluoride, polytrifluoroethylene, polyethylene difluoride, polyethylene vinyl acetate, polychlorotrifluoroethylene and their multi-component copolymers.

[0056] In a specific embodiment of the present invention, the zinc salt is at least one of zinc chloride, zinc acetate, zinc sulfate, zinc nitrate and zinc trifluoromethanesulfonate.

[0057] In a specific embodiment of the present invention, the ionic liquid is at least one of 1-ethyl-3-methylimidazolium zinc nitrate, 1-butyl-trimethylimidazolium zinc nitrate, 1-ethyl-trimethylimidazolium zinc hexafluorophosphate, 1-ethyl-trimethylimidazolium zinc tetrafluoroborate, and 1-ethyl-trimethylimidazolium zinc trifluorosulfonate.

[0058] In a specific embodiment of the present invention, in the piezoelectric high molecular polymer, the mass percentage content of the piezoelectric high molecular weight is 30% to 80%, the mass percentage content of the zinc salt is 5% to 35%, and the mass percentage content of the ionic liquid is 5% to 35%.

[0059] Preferably, the mass percentage content of the piezoelectric polymer is 40% to 70%, the mass percentage content of the zinc salt is 10% to 30%, and the mass percentage content of the ionic liquid is 10% to 30%;

[0060] More preferably, the mass percentage content of the piezoelectric polymer is 50% to 60%, the mass percentage content of the zinc salt is 15% to 25%, and the mass percentage content of the ionic liquid is 15% to 25%.

[0061] Specifically, the mass percentage content of the piezoelectric polymer is 30%, the mass percentage content of the zinc salt is 35%, and the mass percentage content of the ionic liquid is 35%; alternatively, the mass percentage content of the piezoelectric polymer is 40%, the mass percentage content of the zinc salt is 30%, and the mass percentage content of the ionic liquid is 30%; alternatively, the mass percentage content of the piezoelectric polymer is 50%, the mass percentage content of the zinc salt is 25%, and the mass percentage content of the ionic liquid is 25%; alternatively, the mass percentage content of the piezoelectric polymer is 60%, the mass percentage content of the zinc salt is 20%, and the mass percentage content of the ionic liquid is 20%; alternatively, the mass percentage content of the piezoelectric polymer is 70%, the mass percentage content of the zinc salt is 15%, and the mass percentage content of the ionic liquid is 15%; alternatively, the mass percentage content of the piezoelectric polymer is 60%, the mass percentage content of the zinc salt is 20%, and the mass percentage content of the ionic liquid is 20%; alternatively, the mass percentage content of the piezoelectric polymer is 80%, the mass percentage content of the zinc salt is 10%, and the mass percentage content of the ionic liquid is 10%.

[0062] Another embodiment of the present invention provides a method for preparing a solid electrolyte membrane, comprising the following steps:

[0063] The polymer material is dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is subjected to spinning treatment to obtain a nanofiber membrane;

[0064] Using an organic solvent to dissolve the piezoelectric polymer, the zinc salt and the ionic liquid, heating and stirring until the mixture is uniform, to obtain a mixed solution;

[0065] The mixed solution is evenly spread on the nanofiber membrane and dried to obtain a solid electrolyte membrane.

[0066] The present invention introduces the electrostatic spinning technology to prepare the nanofiber membrane, and the mixed solution is evenly spread on the nanofiber membrane. The preparation method is simple and easy to control.

[0067] In a specific implementation of the present invention, a piezoelectric polymer is dissolved in an organic solvent, and heated and stirred on a magnetic heating stirrer until it is completely dissolved; a zinc salt is added to the mixed solution, heated and stirred to completely dissolve it; an ionic liquid is added to the mixed solution, heated and stirred to completely dissolve it, and a mixed solution is obtained.

[0068] In a specific embodiment of the present invention, the spinning process is an electrospinning process, and the conditions of the electrospinning process are as follows:

[0069] The inner diameter of the needle is 0.6-2.2 mm; the voltage is 10-20 kV; the temperature is 35-45 °C, the relative humidity is 43-47% RH, and the propulsion speed is 3-6 mL h-1 , receiving distance is 10-20cm, receiver speed is 100-500rpm;

[0070] Preferably, the inner diameter of the needle is 0.8-2 mm; the voltage is 12-18 kV; the temperature is 37-43° C., the relative humidity is 44-47% RH, and the propulsion speed is 4-6 mL h -1 , receiving distance is 12~18cm, receiver speed is 150~450rpm;

[0071] More preferably, the inner diameter of the needle is 1 to 1.8 mm; the voltage is 14 to 16 kV; the temperature is 39 to 41°C, the relative humidity is 44 to 46% RH, and the advancement speed is 4 to 5 mL h -1 , receiving distance is 14-16cm, receiver speed is 200-400rpm;

[0072] In the spinning solution, the mass concentration of the organic solvent is 80% to 90%, and the mass concentration of the polymer material is 10% to 20%; preferably, the mass concentration of the organic solvent is 82% to 88%, and the mass concentration of the polymer material is 12% to 18%; more preferably, the mass concentration of the organic solvent is 84% ​​to 86%, and the mass concentration of the polymer material is 14% to 16%;

[0073] The organic solvent includes at least one of N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide;

[0074] The heating temperature of the piezoelectric polymer, zinc salt and ionic liquid is 20°C to 95°C, preferably 30°C to 80°C, and more preferably 40°C to 70°C.

[0075] Yet another embodiment of the present invention provides a secondary battery including the above-mentioned solid electrolyte membrane.

[0076] In a specific embodiment of the present invention, the secondary battery is an all-solid-state zinc ion battery, and the solid electrolyte in the all-solid-state zinc ion battery is the solid electrolyte membrane of the present invention.

[0077] The secondary battery provided by the present invention has the advantages of high capacity, excellent cycle performance, and good rate capability, and can be a flexible battery with excellent mechanical properties. Therefore, the secondary battery prepared using the solid electrolyte membrane of the present invention can improve the stability of the electrochemical performance of the secondary battery and extend the life of the secondary battery.

[0078] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0079] 1. Nanofiber piezoelectric polymer composite solid electrolyte membrane embodiment

[0080] Example A1

[0081] This embodiment provides a nanofiber piezoelectric polymer composite solid electrolyte membrane and a preparation method thereof. Figure 1 shown.

[0082] The preparation method of the nanofiber piezoelectric polymer composite solid electrolyte membrane comprises the following steps:

[0083] S1. Weigh 3.2 g of polyimide polymer (molecular weight 14w) and dissolve it in N,N-dimethylformamide to prepare a polymer solution with a certain concentration, wherein the mass concentration of polyimide in the spinning solution is 16%.

[0084] S2. Inject the spinning solution prepared in step S1 into a syringe with stainless steel needles of different models, adjust the voltage, temperature and humidity, propulsion speed, receiving distance, receiver speed and other parameters, and perform electrostatic spinning to form a polyimide nanofiber membrane; wherein the stainless steel needle for electrostatic spinning has a specification of 12G to 20G, that is, the inner diameter of the needle is 0.6 to 2.2mm; the voltage is 25kV; the temperature is controlled at 45±2℃, the relative humidity is controlled at 45±2%RH, and the propulsion speed is 5mL h -1 , receiving distance is 15cm, receiver speed is 500rpm.

[0085] S3. Weigh 6 g of polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer, add it to 30 mL of organic solvent N, N-dimethylformamide, and continue heating and stirring at a constant temperature of 50 ° C until the copolymer is completely dissolved, and the resulting solution is a colorless, transparent liquid with a certain viscosity;

[0086] S4. Add 2.4 g of zinc salt zinc trifluoromethanesulfonate to the colorless, transparent, viscous liquid obtained in step S3 above, and continue heating and stirring at 50 ° C until the zinc trifluoromethanesulfonate is completely dissolved in the solution, so that the final solution is still a colorless, transparent, and viscous liquid;

[0087] S5. Add 0.96 g of ionic liquid 1-ethyl-trimethylimidazolium trifluorosulfonate zinc to the solution obtained in step S4, and continue heating and stirring at a constant temperature of 50 ° C to ensure that all components are completely dissolved, and finally obtain a colorless, transparent and viscous solution;

[0088] S6. The polyimide nanofiber membrane prepared in the above step S2 is evenly spread on a glass plate, and then the colorless transparent viscous liquid obtained in step S5 is evenly coated on the surface of the spread polyimide nanofiber membrane, followed by standing at room temperature for 60 minutes to allow the solvent to fully evaporate. After the solvent is completely evaporated, a piezoelectric polymer composite solid electrolyte membrane with a nanofiber structure can be obtained.

[0089] Example A2

[0090] This embodiment provides a nanofiber piezoelectric polymer composite solid electrolyte membrane and a preparation method thereof. The preparation method of the nanofiber piezoelectric polymer composite solid electrolyte membrane comprises the following steps:

[0091] S1. Weigh 2.4 g of polyamide-imide polymer (molecular weight 3w) and dissolve it in N,N-dimethylformamide to prepare a polymer solution with a certain concentration, wherein the mass concentration of polyimide in the spinning solution is 12%.

[0092] S2. Inject the spinning solution prepared in step S1 into a syringe with stainless steel needles of different models, adjust the voltage, temperature and humidity, propulsion speed, receiving distance, receiver speed and other parameters, and perform electrostatic spinning to form a polyimide nanofiber membrane; wherein the stainless steel needle for electrostatic spinning has a specification of 12G to 20G, that is, the inner diameter of the needle is 0.6 to 2.2mm; the voltage is 25kV; the temperature is controlled at 45±2℃, the relative humidity is controlled at 45±2%RH, and the propulsion speed is 5mL h -1 , receiving distance is 15cm, receiver speed is 500rpm.

[0093] S3. Weigh 6 g of polytrifluoroethylene and add it to 30 mL of an organic solvent, N, N-dimethylformamide, and continue heating and stirring at a constant temperature of 60 ° C until the copolymer is completely dissolved, and the resulting solution is a colorless, transparent liquid with a certain viscosity;

[0094] S4. Add 2.4 g of zinc chloride, a zinc salt, to the colorless, transparent, viscous liquid obtained in step S3 above, and continue heating and stirring at 60° C. until the zinc chloride is completely dissolved in the solution, so that the resulting solution is still a colorless, transparent, and viscous liquid;

[0095] S5. Add 0.48 g of ionic liquid 1-butyl-trimethylimidazolium zinc nitrate to the solution obtained in step S4, continue heating and stirring at a constant temperature of 60 ° C to ensure that all components are completely dissolved, and finally obtain a colorless, transparent and viscous solution;

[0096] S6. The nanofiber membrane prepared in the above step S2 is evenly spread on a glass plate, and then the colorless transparent viscous liquid obtained in step S5 is evenly coated on the surface of the spread nanofiber membrane, followed by standing at room temperature for 60 minutes to allow the solvent to fully evaporate. After the solvent is completely evaporated, a piezoelectric polymer composite solid electrolyte membrane with a nanofiber structure can be obtained.

[0097] Example A3

[0098] This embodiment provides a nanofiber piezoelectric polymer composite solid electrolyte membrane and a preparation method thereof. The preparation method of the nanofiber piezoelectric polymer composite solid electrolyte membrane comprises the following steps:

[0099] S1. Weigh 2.8 g of polyethylene oxide polymer (molecular weight 20w) and dissolve it in N,N-dimethylformamide to prepare a polymer solution with a certain concentration, wherein the mass concentration of polyimide in the spinning solution is 14%.

[0100] S2. Inject the spinning solution prepared in step S1 into a syringe with stainless steel needles of different models, adjust the voltage, temperature and humidity, propulsion speed, receiving distance, receiver speed and other parameters, and perform electrostatic spinning to form a polyimide nanofiber membrane; wherein the stainless steel needle for electrostatic spinning has a specification of 12G to 20G, that is, the inner diameter of the needle is 0.6 to 2.2mm; the voltage is 25kV; the temperature is controlled at 45±2℃, the relative humidity is controlled at 45±2%RH, and the propulsion speed is 5mL h -1 , receiving distance is 15cm, receiver speed is 500rpm.

[0101] S3. Weigh 6 g of polyethylene difluoride, add it to 30 mL of organic solvent N, N-dimethylformamide, and continue heating and stirring at a constant temperature of 70 ° C until the copolymer is completely dissolved, and the resulting solution is a colorless, transparent liquid with a certain viscosity;

[0102] S4. Add 2.4 g of zinc acetate, a zinc salt, to the colorless, transparent, viscous liquid obtained in step S3 above, and continue heating and stirring at 70° C. until the zinc acetate is completely dissolved in the solution, so that the final solution is still a colorless, transparent, and viscous liquid;

[0103] S5. Add 1.44 g of ionic liquid 1-ethyl-trimethylimidazolium zinc hexafluorophosphate to the solution obtained in step S4, and continue heating and stirring at a constant temperature of 70 ° C to ensure that all components are completely dissolved, and finally obtain a colorless, transparent and viscous solution;

[0104] S6. The nanofiber membrane prepared in the above step S2 is evenly spread on a glass plate, and then the colorless transparent viscous liquid obtained in step S5 is evenly coated on the surface of the spread nanofiber membrane, followed by standing at room temperature for 60 minutes to allow the solvent to fully evaporate. After the solvent is completely evaporated, a piezoelectric polymer composite solid electrolyte membrane with a nanofiber structure can be obtained.

[0105] Example A4

[0106] This embodiment provides a nanofiber piezoelectric polymer composite solid electrolyte membrane and a preparation method thereof. The preparation method of the nanofiber piezoelectric polymer composite solid electrolyte membrane comprises the following steps:

[0107] S1. Weigh 3.6 g of polyvinyl alcohol polymer (molecular weight 14w) and dissolve it in N,N-dimethylformamide to prepare a polymer solution with a certain concentration, wherein the mass concentration of polyimide in the spinning solution is 18%.

[0108] S2. Inject the spinning solution prepared in step S1 into a syringe with stainless steel needles of different models, adjust the voltage, temperature and humidity, propulsion speed, receiving distance, receiver speed and other parameters, and perform electrostatic spinning to form a polyimide nanofiber membrane; wherein the stainless steel needle for electrostatic spinning has a specification of 12G to 20G, that is, the inner diameter of the needle is 0.6 to 2.2mm; the voltage is 25kV; the temperature is controlled at 45±2℃, the relative humidity is controlled at 45±2%RH, and the propulsion speed is 5mL h -1 , receiving distance is 15cm, receiver speed is 500rpm.

[0109] S3. Weigh 6 g of polyethylene vinyl acetate and add it to 30 mL of an organic solvent, N, N-dimethylformamide, and continue heating and stirring at a constant temperature of 80 ° C until the copolymer is completely dissolved, and the resulting solution is a colorless, transparent liquid with a certain viscosity;

[0110] S4. Add 1.2 g of zinc salt zinc nitrate to the colorless, transparent, viscous liquid obtained in step S3 above, and continue heating and stirring at 80° C. until the zinc nitrate is completely dissolved in the solution, so that the final solution is still a colorless, transparent, and viscous liquid;

[0111] S5. Add 0.96 g of ionic liquid 1-ethyl-3-methylimidazole zinc nitrate to the solution obtained in step S4, continue heating and stirring at a constant temperature of 80 ° C to ensure that all components are completely dissolved, and finally obtain a colorless, transparent and viscous solution;

[0112] S6. The nanofiber membrane prepared in the above step S2 is evenly spread on a glass plate, and then the colorless transparent viscous liquid obtained in step S5 is evenly coated on the surface of the spread nanofiber membrane, followed by standing at room temperature for 60 minutes to allow the solvent to fully evaporate. After the solvent is completely evaporated, a piezoelectric polymer composite solid electrolyte membrane with a nanofiber structure can be obtained.

[0113] Example A5

[0114] This embodiment provides a nanofiber piezoelectric polymer composite solid electrolyte membrane and a preparation method thereof. The preparation method of the nanofiber piezoelectric polymer composite solid electrolyte membrane comprises the following steps:

[0115] S1. Weigh 4 g of polymethyl methacrylate polymer (molecular weight 60w) and dissolve it in N,N-dimethylformamide to prepare a polymer solution with a certain concentration, wherein the mass concentration of polyimide in the spinning solution is 20%.

[0116] S2. Inject the spinning solution prepared in step S1 into a syringe with stainless steel needles of different models, adjust the voltage, temperature and humidity, propulsion speed, receiving distance, receiver speed and other parameters, and perform electrostatic spinning to form a polyimide nanofiber membrane; wherein the stainless steel needle for electrostatic spinning has a specification of 12G to 20G, that is, the inner diameter of the needle is 0.6 to 2.2mm; the voltage is 25kV; the temperature is controlled at 45±2℃, the relative humidity is controlled at 45±2%RH, and the propulsion speed is 5mL h -1 , receiving distance is 15cm, receiver speed is 500rpm.

[0117] S3. Weigh 6 g of polyethylene difluoride and add it to 30 mL of an organic solvent, N, N-dimethylformamide, and continue heating and stirring at a constant temperature of 90 ° C until the copolymer is completely dissolved, and the resulting solution is a colorless, transparent liquid with a certain viscosity;

[0118] S4. Add 3.4 g of zinc sulfate, a zinc salt, to the colorless, transparent, viscous liquid obtained in step S3 above, and continue heating and stirring at 90° C. until the zinc sulfate is completely dissolved in the solution, so that the resulting solution is still a colorless, transparent, and viscous liquid;

[0119] S5. Add 0.96 g of ionic liquid 1-ethyl-trimethylimidazolium zinc tetrafluoroborate to the solution obtained in step S4, and continue heating and stirring at a constant temperature of 90 ° C to ensure that all components are completely dissolved, and finally obtain a colorless, transparent and viscous solution;

[0120] S6. The nanofiber membrane prepared in the above step S2 is evenly spread on a glass plate, and then the colorless transparent viscous liquid obtained in step S5 is evenly coated on the surface of the spread nanofiber membrane, followed by standing at room temperature for 60 minutes to allow the solvent to fully evaporate. After the solvent is completely evaporated, a piezoelectric polymer composite solid electrolyte membrane with a nanofiber structure can be obtained.

[0121] Comparative Example A1

[0122] This comparative example provides a piezoelectric polymer solid electrolyte membrane and a preparation method thereof. The prepared nanofiber piezoelectric polymer composite solid electrolyte membrane is Figure 2 As shown. The difference compared with Example A1 is that the polyimide nanofiber membrane is not included. The preparation method of the piezoelectric polymer electrolyte membrane comprises the following steps:

[0123] S1. Weigh 6 g of polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer, add it to 30 mL of organic solvent N, N-dimethylformamide, and continue heating and stirring at a constant temperature of 50° C. until the copolymer is completely dissolved, and the resulting solution is a colorless, transparent liquid with a certain viscosity;

[0124] S2. Add 2.4 g of zinc salt zinc trifluoromethanesulfonate to the colorless, transparent, viscous liquid obtained in step S1 above, and continue heating and stirring at 50° C. until the zinc trifluoromethanesulfonate is completely dissolved in the solution, so that the final solution is still a colorless, transparent, and viscous liquid;

[0125] S3. Add 0.96 g of ionic liquid 1-ethyl-trimethylimidazolium trifluorosulfonate zinc to the solution obtained in step S2, and continue heating and stirring at a constant temperature of 50 ° C to ensure that all components are completely dissolved, and finally obtain a colorless, transparent and viscous solution;

[0126] S4. The colorless, transparent, viscous liquid obtained in step S3 is evenly coated on a glass plate / culture dish, and then allowed to stand at room temperature for 30 to 60 minutes to allow the solvent to fully evaporate. After the solvent is completely evaporated, a piezoelectric polymer solid electrolyte membrane can be obtained.

[0127] Comparative Example A2

[0128] This comparative example provides a piezoelectric polymer solid electrolyte membrane and a preparation method thereof. Compared with Example A1, the difference is that the amount of ionic liquid added is modified to 0.2 g. The preparation method of the piezoelectric polymer electrolyte membrane is prepared by referring to the method for preparing a piezoelectric polymer solid electrolyte membrane in Comparative Example A1.

[0129] Comparative Example A3

[0130] This comparative example provides a piezoelectric polymer solid electrolyte membrane and a preparation method thereof. Compared with Example A1, the difference is that the amount of ionic liquid added is modified to 5g. The preparation method of the piezoelectric polymer electrolyte membrane is prepared by referring to the method for preparing a piezoelectric polymer solid electrolyte membrane in Comparative Example A1.

[0131] Comparative Example A4

[0132] This comparative example provides a piezoelectric polymer solid electrolyte membrane and a preparation method thereof. The prepared nanofiber piezoelectric polymer composite solid electrolyte membrane is Figure 3 As shown. The difference compared with Example A1 is that it does not contain polyimide nanofiber membrane and ionic liquid. The preparation method of the piezoelectric polymer electrolyte membrane comprises the following steps:

[0133] S1. Weigh 6 g of polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene terpolymer, add it to 30 mL of organic solvent N, N-dimethylformamide, and continue heating and stirring at a constant temperature of 50° C. until the copolymer is completely dissolved, and the resulting solution is a colorless, transparent liquid with a certain viscosity;

[0134] S2. Add 2.4 g of zinc salt zinc trifluoromethanesulfonate to the colorless, transparent, viscous liquid obtained in step S1 above, and continue heating and stirring at 50° C. until the zinc trifluoromethanesulfonate is completely dissolved in the solution, so that the final solution is still a colorless, transparent, and viscous liquid;

[0135] S3. The colorless, transparent, viscous liquid obtained in step S2 is evenly coated on a glass plate / culture dish, and then allowed to stand at room temperature for 30 to 60 minutes to allow the solvent to fully evaporate. After the solvent is completely evaporated, a piezoelectric polymer solid electrolyte membrane can be obtained.

[0136] Comparative Example A5

[0137] This comparative example provides a piezoelectric polymer solid electrolyte membrane and a preparation method thereof. Compared with Example A1, the difference is that the amount of zinc salt added is modified to 0.3g. The preparation method of the piezoelectric polymer electrolyte membrane is prepared by referring to the method for preparing a piezoelectric polymer solid electrolyte membrane in Comparative Example A4.

[0138] Comparative Example A6

[0139] This comparative example provides a piezoelectric polymer solid electrolyte membrane and a preparation method thereof. The difference compared with Example A1 is that the amount of zinc salt added is modified to 5g. The preparation method of the piezoelectric polymer electrolyte membrane is prepared by referring to the method for preparing a piezoelectric polymer solid electrolyte membrane in Comparative Example A4.

[0140] Comparative Example A7

[0141] This comparative example provides a nanofiber and piezoelectric high molecular polymer solid electrolyte membrane and a preparation method thereof. The difference compared with Example A1 is that no ionic liquid is included. The preparation method of the nanofiber and piezoelectric high molecular polymer electrolyte membrane is prepared by referring to the method for preparing the nanofiber and piezoelectric high molecular polymer solid electrolyte membrane of Example A1.

[0142] 2. Zinc Ion Battery Example

[0143] Example B1

[0144] Embodiment B1 provides a zinc ion battery, and the zinc ion battery is assembled according to the following method:

[0145] Preparation of solid electrolyte membrane: Cut the solid electrolyte membrane composited with nanofibers and piezoelectric polymers provided in Example A1 into a shape and size suitable for installation in a button cell;

[0146] Positive electrode: Cut the 200mm thick zinc foil into a shape and size suitable for installation in button batteries;

[0147] Negative electrode: Cut the 200mm thick zinc foil into a shape and size suitable for installation in button batteries;

[0148] Assembly of zinc ion battery: The solid electrolyte membrane composite of nanofibers and piezoelectric polymers provided in Example A1 is assembled together with the above-cut positive electrode sheet and negative electrode sheet to form the zinc ion battery in Example B1.

[0149] Example B2

[0150] Embodiment B2 provides a zinc-iodine battery, and the zinc-iodine battery is assembled into a zinc-iodine battery according to the following method:

[0151] Preparation of solid electrolyte membrane: Cut the solid electrolyte membrane composited with nanofibers and piezoelectric polymers provided in Example A1 into a shape and size suitable for installation in a button cell;

[0152] Preparation of positive electrode sheet: The positive electrode sheet is prepared according to the following steps: activated carbon, conductive carbon and polyvinylidene fluoride are mixed evenly in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone is added and dispersed evenly to obtain activated carbon slurry. The activated carbon slurry is evenly coated on graphite paper to prepare an activated carbon electrode sheet. The activated carbon electrode sheet is then placed in iodine vapor for adsorption for 12 hours to obtain an iodine positive electrode, which is used as the positive electrode of the zinc-iodine battery.

[0153] Negative electrode: Cut the 200mm thick zinc foil into a shape and size suitable for installation in button batteries;

[0154] Assembly of zinc-iodine battery: The solid electrolyte membrane composite of nanofibers and piezoelectric polymers provided in Example A1 is assembled together with the above-mentioned positive electrode sheet and negative electrode sheet to form the zinc-iodine battery in Example B2.

[0155] Example B3

[0156] Embodiment B3 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Embodiment B2, except that the solid electrolyte provided in Embodiment A2 is used.

[0157] Example B4

[0158] Embodiment B4 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Embodiment B2, except that the solid electrolyte provided in Embodiment A3 is used.

[0159] Example B5

[0160] Embodiment B5 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Embodiment B2, except that the solid electrolyte provided in Embodiment A4 is used.

[0161] Comparative Example B1

[0162] Comparative Example B1 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Example B2, except that the solid electrolyte provided in Comparative Example A1 is used.

[0163] Comparative Example B2

[0164] Comparative Example B2 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Example B2, except that the solid electrolyte provided in Comparative Example A2 is used.

[0165] Comparative Example B3

[0166] Comparative Example B3 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Example B2, except that the solid electrolyte provided in Comparative Example A3 is used.

[0167] Comparative Example B4

[0168] Comparative Example B4 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Example B2, except that the solid electrolyte provided in Comparative Example A4 is used.

[0169] Comparative Example B5

[0170] Comparative Example B5 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Example B2, except that the solid electrolyte provided in Comparative Example A5 is used.

[0171] Comparative Example B6

[0172] Comparative Example B6 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Example B2, except that the solid electrolyte provided in Comparative Example A6 is used.

[0173] Comparative Example B7

[0174] Comparative Example B7 provides a zinc-iodine battery. The assembly method of the zinc-ion battery is the same as that of Example B2, except that the solid electrolyte provided in Comparative Example A7 is used.

[0175] Related characteristics test

[0176] 1. Structural characterization of solid electrolyte membranes composited with nanofibers and piezoelectric polymers:

[0177] The solid electrolyte membranes of nanofibers and piezoelectric polymers in Example A1 and Comparative Example A7 were subjected to SEM analysis: The SEM images of the solid electrolyte membranes of nanofibers and piezoelectric polymers in Example A1 are as follows: Figure 5 As shown, the SEN diagram of the solid electrolyte membrane composited with nanofibers and piezoelectric polymers in Comparative Example A7 is as follows Figure 4 As shown. According to the SEM image, the solid electrolyte membrane composited with nanofibers and piezoelectric polymers in the embodiment of the present application has a complete nanofiber structure. These nanofibers act as nano-skeletons in the solid electrolyte membrane, and their surfaces are covered with ionic liquids, forming a loose and porous ion conduction space, thereby significantly improving the ion conductivity. However, the solid electrolyte membrane composited with nanofibers and piezoelectric polymers in Comparative Example A7 has problems such as poor interface contact, severe zinc dendrite growth, aggravated battery hydrogen evolution, and decreased battery stability. This shows that the addition of ionic liquids can significantly improve the ion conductivity and build a stable reaction interface.

[0178] Example A1 (corresponding to Figure 7 The solid electrolyte membrane of the nanofiber and piezoelectric polymer composite in the piezoelectric polymer-ionic liquid-nanofiber) is different from that in the comparative example A1 (corresponding to Figure 7 piezoelectric polymer-ionic liquid) and A4 (corresponding to Figure 7 The XRD patterns of the nanofiber and piezoelectric polymer composite solid electrolyte membrane in Example A1 and the piezoelectric polymer solid electrolyte membrane in Comparative Examples A1 and A4 are compared. Figure 7 As shown. It can be seen from the XRD spectrum that the solid electrolyte membrane composite of nanofibers and piezoelectric polymers in the embodiment of the present application has the same peak position as the piezoelectric polymer solid electrolyte membrane in the comparative example, but the carbon element peaks of the three samples have changed. This is due to the addition of ionic liquids and nanofibers. The ionic liquid contains multiple carbon-containing groups such as methyl, ethyl, and imidazole, so the carbon peak is strengthened; the nanofibers contain carbon-containing groups such as imide rings, which also leads to the strengthening of the carbon peak. Therefore, the enhancement of the carbon peak in the figure shows that ionic liquids and nanofibers have been successfully introduced into Example A1, and are well combined. No new peaks appear, indicating that the electrolyte membrane in Example A1 of the present application has high purity.

[0179] Example A1 (corresponding to Figure 8 The solid electrolyte membrane of nanofiber and piezoelectric polymer composite in piezoelectric polymer-ionic liquid-nanofiber) and comparative example A1 (corresponding to Figure 8 piezoelectric polymer-ionic liquid) and A4 (corresponding to Figure 8 The piezoelectric polymer solid electrolyte membrane in the piezoelectric polymer in the embodiment A1 is subjected to Raman spectroscopy (Raman) analysis: the Raman spectrum comparison diagram of the solid electrolyte membrane of the nanofiber and piezoelectric polymer composite in the embodiment A1 and the piezoelectric polymer solid electrolyte membrane in the comparative examples A1 and A4 is as shown in Figure 8 As shown in the Raman spectrum, the solid electrolyte membrane composed of nanofibers and piezoelectric polymers in the embodiment of the present application has a peak at 759.2 cm -1 、1032.2cm -1 and 1426.7cm -1 There are obvious characteristic peaks, which correspond to the CH bonds in polyimide and 1-ethyl-3-methylimidazole (759.2 cm -1 ), zinc trifluoromethanesulfonate and 1-ethyl-trimethylimidazolium trifluorosulfonate zinc C-S bond (1032.2 cm -1 ), polyimide and CN bonds in 1-ethyl-3-methylimidazole (1426.7 cm -1 ). These characteristic peaks further prove the uniform mixing of nanofibers, piezoelectric polymers and zinc salts in the composite solid electrolyte membrane.

[0180] The electrochemical stability of the nanofiber and piezoelectric polymer composite solid electrolyte membrane in Example A1 and the piezoelectric polymer solid electrolyte membrane in Comparative Examples A1 and A4 was analyzed: Example A1 (corresponding to Fig. 9The nanofiber and piezoelectric polymer composite solid electrolyte membrane in PI-PTC-IL) and the comparative example A1 (corresponding to Fig. 9 PTC-IL) and A4 (corresponding to Fig. 9 The electrochemical stability comparison of the piezoelectric polymer solid electrolyte membrane in the PTC Fig. 9 As shown in the electrochemical stability comparison diagram, it can be seen that the nanofiber and piezoelectric polymer composite solid electrolyte membrane in Example A1 has a higher voltage stability window than the piezoelectric polymer solid electrolyte membranes in Comparative Examples A1 and A4. This proves the strong stability of the nanofiber and piezoelectric polymer composite solid electrolyte membrane in the embodiment.

[0181] The solid electrolyte membrane of the nanofiber and piezoelectric polymer composite in Example A1 was tested for ionic conductivity: The ionic conductivity of the solid electrolyte membrane of the nanofiber and piezoelectric polymer composite in Example A1 is shown in FIG. Fig.10 As shown in the ionic conductivity graph, it can be seen that the solid electrolyte membrane composited with nanofibers and piezoelectric polymers in the embodiment still maintains excellent ionic conductivity at high temperatures, and the ionic conductivity of the membrane tends to be stable when the temperature changes. It is proved that the solid electrolyte membrane composited with nanofibers and piezoelectric polymers in the embodiment has excellent thermal stability and excellent conductive properties.

[0182] 2. Zinc ion battery chemical performance test:

[0183] The zinc ion battery in Example B1 was tested for high current cycle stability, high and low temperature adaptability, and dielectric constant; the zinc iodine battery in Example B2 was tested for high current cycle stability. The test conditions for the cycle stability and high and low temperature of the zinc ion battery and the cycle stability test conditions of the zinc iodine battery are as follows:

[0184] The high current cycle test of zinc ion battery is mainly carried out at 5mAcm -2 The key current is used for constant current charge and discharge test. The high and low temperature test is used to measure the stability of the battery by changing the temperature of the battery test during the battery cycle. The temperature range is -30℃ to 30℃. The cycle test of zinc-iodine battery is mainly carried out at 5mAcm -2 The key current is used for constant current charge and discharge test.

[0185] Among them, the cycle performance curve of the zinc ion battery in Example B1 is as follows Fig.11 As shown, the high and low temperature performance curve is as follows Fig.12 The dielectric constant curve is shown in Figure 6 As shown; the cycle performance curve of the zinc-iodine battery in Example B2 is as shown Fig.13 shown by Figures 11 to 13It can be seen that the zinc ion battery and the zinc iodine battery can be stably cycled and stably cycled for 36,500 times at a current density of 5 A / g, with a retention rate of 95.37%, indicating that the new zinc ion solid electrolyte membrane designed by the present invention is very effective in inhibiting the decomposition of iodine and improving the cycle efficiency of zinc iodine batteries, further verifying the potential of the polyimide fiber network in maintaining the stability of the electrolyte membrane.

[0186] It can be seen from the cycle performance test, high and low temperature performance test and dielectric constant test results that the zinc ion battery in the embodiment of the present application shows high capacity, strong conductivity and stable cycle performance. Especially under high current conditions, the battery still maintains stable cycle performance. At the same time, the battery also has excellent cycle performance under low temperature conditions. This shows that the solid electrolyte membrane of nanofiber and piezoelectric polymer composite in the embodiment of the present application as an electrolyte significantly enhances the structural stability of the zinc ion battery during the charge and discharge process and effectively inhibits the corrosion of zinc. The electrolyte membrane gives the battery high capacity, high conductivity and strong low temperature resistance, so that the battery has excellent capacity characteristics and excellent low temperature performance.

[0187] The performance of the batteries prepared in Examples B2 to B5 and Comparative Examples B1 to B7 was tested, and the results are shown in Table 1.

[0188] Table 1

[0189]

[0190]

[0191] It can be seen from Table 1 that the batteries prepared in Examples B2 to B5 have the characteristics of high capacity and excellent cycle performance. Compared with the comparative examples, it can be seen that the specific capacity of Example B2 is better than that of Comparative Example B1 (excluding polyimide nanofiber membrane), Comparative Example B2 (less ionic liquid added), Comparative Example B4 (excluding polyimide nanofiber membrane and ionic liquid), Comparative Example B5 (less zinc salt added), Comparative Example B6 (more zinc salt added) and Comparative Example B7 (excluding ionic liquid), and the cycle retention rate of Example B2 is better than that of Comparative Example B1 (excluding polyimide nanofiber membrane), Comparative Example B2 (less ionic liquid added), Comparative Example B3 (more ionic liquid added), Comparative Example B4 (excluding polyimide nanofiber membrane and ionic liquid), Comparative Example B5 (less zinc salt added), Comparative Example B6 (more zinc salt added) and Comparative Example B7 (excluding ionic liquid). This shows that whether a polyimide nanofiber membrane is included, whether an ionic liquid is included, and the amount of ionic liquid and the amount of zinc salt added will affect the capacity and cycle performance of the battery.

[0192] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A solid electrolyte membrane composite of nanofibers and piezoelectric polymers, characterized in that: The preparation raw materials include nanofibers and piezoelectric high molecular polymers, and the preparation raw materials of the piezoelectric high molecular polymer include piezoelectric high molecular, zinc salt and ionic liquid; The nanofibers are in the form of nanofiber membranes as the skeleton of the solid electrolyte membrane, and the piezoelectric high molecular polymer is arranged on the nanofiber membrane to form the solid electrolyte membrane.

2. The solid electrolyte membrane according to claim 1, characterized in that The mass ratio of the nanofiber to the piezoelectric high molecular polymer is 1:2 to 1:

10.

3. The solid electrolyte membrane according to claim 1, characterized in that The nanofiber is at least one of polyester, polyamide, polyimide, polyamide-amide, polyimide-amide, polyamide-imide, polyamide-amide-amide, polyvinyl alcohol, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, and polyurethane polymer materials.

4. The solid electrolyte membrane according to claim 1, characterized in that The piezoelectric polymer is at least one of polystyrene, polyvinylidene fluoride, polytrifluoroethylene, polyethylene difluoride, polyethylene vinyl acetate, polychlorotrifluoroethylene and multi-component copolymers thereof.

5. The solid electrolyte membrane according to claim 1, characterized in that The zinc salt is at least one of zinc chloride, zinc acetate, zinc sulfate, zinc nitrate and zinc trifluoromethanesulfonate.

6. The solid electrolyte membrane according to claim 1, characterized in that The ionic liquid is at least one of 1-ethyl-3-methylimidazole zinc nitrate, 1-butyl-trimethylimidazole zinc nitrate, 1-ethyl-trimethylimidazole zinc hexafluorophosphate, 1-ethyl-trimethylimidazole zinc tetrafluoroborate, and 1-ethyl-trimethylimidazole zinc trifluorosulfonate.

7. The solid electrolyte membrane according to claim 1, characterized in that The raw materials for preparing the piezoelectric macromolecular polymer have the following contents: the mass percentage of the piezoelectric macromolecular polymer is 30% to 80%, the mass percentage of the zinc salt is 5% to 35%, and the mass percentage of the ionic liquid is 5% to 35%.

8. The method for preparing a solid electrolyte membrane according to any one of claims 1 to 7, comprising the following steps: The polymer material is dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is subjected to spinning treatment to obtain a nanofiber membrane; Using an organic solvent to dissolve the piezoelectric polymer, the zinc salt and the ionic liquid, heating and stirring until the mixture is uniform, to obtain a mixed solution; The mixed solution is evenly spread on the nanofiber membrane and dried to obtain a solid electrolyte membrane.

9. The preparation method according to claim 8, characterized in that: The spinning process is an electrostatic spinning process, and the conditions of the electrostatic spinning process are as follows: The inner diameter of the needle is 0.6-2.2 mm; the voltage is 10-20 kV; the temperature is 35-45 °C, the relative humidity is 43-47% RH, and the propulsion speed is 3-6 mL h -1 , receiving distance is 10-20cm, receiver speed is 100-500rpm; and / or In the spinning solution, the mass concentration of the organic solvent is 80% to 90%, and the mass concentration of the polymer material is 10% to 20%; and / or The organic solvent comprises at least one of N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide; and / or The heating temperature of the piezoelectric polymer, zinc salt and ionic liquid is 20°C to 95°C.

10. A secondary battery, characterized in that: The invention comprises a solid electrolyte membrane as claimed in any one of claims 1 to 7 or a solid electrolyte membrane prepared by the method as claimed in any one of claims 8 to 9.

Citation Information

Patent Citations

  • Solid electrolyte and application thereof

    CN111446497A

  • PEO-based solid electrolyte as well as preparation method and application thereof

    CN113270639A

  • Nanofiber polyvinylidene fluoride-based composite solid electrolyte and preparation method and application thereof

    CN114094179A

  • Electrospun composite separator for electrochemical devices and applications of same

    US20200220219A1